Fitting of cochlear implant systems Anpassung von Cochleaimplantatsystemen - Baumann, Uwe; Weißgerber, Tobias; Hoppe, Ulrich (HNO, 2025)
The technical fitting of cochlear implant (CI) systems is a central component of the CI care process. On the one hand, this consists of a standardized procedure, while on the other, the individual needs of the patient are taken into account. It starts with the “initial fitting” during basic therapy, where the initial focus is on achieving a satisfactory impression of sound and loudness. In the follow-up therapy, fine adjustment is carried out to achieve the best possible speech perception in quiet and in noise. The aim is to individually adjust the CI processor to audiological targets. The fitting is carried out by a specially qualified professional in accordance with the German CI fitting guidelines and takes into account anatomical conditions, electrophysiological measurements, and audiological evaluation data. The CI fitting should maintain hearing and speech perception throughout life, thus ensuring a significant improvement in quality of life. In children, achieving the best possible CI fitting is fundamental to facilitating normal speech development.
CRIS-Team Scopus Importer:2025-04-18
Keywords: Cochlear implants; Implantable neurostimulators; Prostheses and implants; Rehabilitation; Verification